Fucosyltransferase VII promotes proliferation via the EGFR/AKT/mTOR pathway in A549 cells - Liang J (OncoTargets and Therapy, 2017)
Jin-xiao Liang,1 Wei Gao,2 Lei Cai1 1Department of Thoracic Surgery, Zhejiang Cancer Hospital, 2School of Medicine, Zhejiang University City College, Hangzhou, People’s Republic of China Abstract: Fucosyltransferase VII (FUT7) is one of a1,3-fucosyltransferases family that catalyzes the final fucosylation step in the synthesis of Lewis antigens and generates a unique glycosylated product sialyl Lewis X (sLeX). sLeX can serve as ligands for E- or P-selectin expressed on the cell surface and results in cancer metastasis and angiogenesis. However, the molecular biological mechanisms of FUT7 elevation in neoplastic cells are still largely unknown. In this study, we examined the impact of FUT7 on cell proliferation and migration in A549 cells by colony formation assay, cell cycle assay, gelatin zymography, wound-healing assay, transwell invasion assay and Western blot. In addition, we identified that FUT7 activated EGFR/AKT/mTOR signal pathway that correlated with sLeX augmentation. In conclusion, FUT7 overexpression augments sLeX synthesis to trigger cell proliferation via the activation of EGFR/AKT/mTOR signaling pathway, which indicated that FUT7 may be a potential therapeutic target for epithelial cancers with a high expression of FUT7 and sLeX. Keywords: fucosyltransferase VII, epidermal growth factor receptor, lung cancer, proliferation, signal pathway